Understanding the Relationship between Trauma Exposure and Depression among Adolescents after Earthquake: The Roles of Fear and Resilience - Zhou, Xiao; Wu, Xinchun; An, Yuanyuan (Frontiers in Psychology, 2016)
Middle school students (N=1435) were assessed eighteen months after the Wenchuan earthquake using measures of trauma exposure, fear, resilience, and depression, to examine the effects of fear and resilience on the relationship between trauma exposure and depression. Fear mediated the relationship between trauma exposure and depression, whereas resilience moderated the relationship between fear and depression. These findings suggest that trauma exposure has a direct positive impact on depression, but also indirectly affects depression through fear. Moreover, fear positively predicted depression under conditions of low resilience, whereas this effect was not significant when resilience was high. These results are discussed in terms of their implications for adolescents after trauma.